Changes in Pattern and Multifocal Electroretinogram in Tuberculosis Patient with Ethambutol Therapy - Syntia Nusanti; Budiman Bintang Prakoso; Muhamad Sidik; Erlina Burhan; Aria Kekalih (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Tuberculosis (TB) is a world health problem, especially in Indonesia as the third biggest country for new emerging TB patients. Ethambutol is one of the standard therapies to treat TB patients in Indonesia. Ethambutol has a side effect called ethambutol optic neuropathy which is hard to diagnose due to normal fundus appearance in most cases and therefore often detected late. Early detection is necessary so that permanent damage can be prevented. Examination pattern electroretinography (pERG) and multifocal electroretinography (mfERG) have the advantage to detect and confirm ocular toxicity by ethambutol after the clinical problem had emerged. It is not yet known neither pERG nor mfERG could detect any changes to detect ethambutol ocular toxicity before the clinical problem emerged. Methods: This study was a prospective clinical trial with 40 eyes samples and analyzed with paired t and Wilcoxon tests. The ocular examination was conducted using the Snellen chart, HRR Richmond Plates, Pelli Robson, pERG, and mfERG in tuberculosis category 1 patient with 2 months follow-up. Result: Visual acuity, color, and contrast sensitivity were normal in all patients for 2 months follow-up period. In pERG examination, the mean implicit time wave P50 was shortened by -1.27± 4.71 mS (p=0.049), and the mean amplitude wave N95 was reduced by -0.93± 4.49 ?V (p=0.038). Both were statistically significant. In the mfERG examination, we did not find any statistically significant changes in both wave N1 and P1. Conclusion: Changes in pattern ERG presented earlier compared to mfERG after ethambutol therapy for 2 months.